Unsteady Separated Mixed Convection Stagnation-Point Flow: The Case of Assisting Flow - Lok , Y. Y.; Pop, I. (International Business Academics Consortium (iBAC), Taipei, Taiwan, 2015)
The problem of unsteady separated stagnation-point flow in mixed convection is studied. Only the case of assisting flow is considered here. By employing similarity transformation, the governing partial differential equations are reduced to a system of ordinary differential equations which are then solved numerically using bvp4c Matlab program. Comparison with results for the steady-state case from the open literature shows good agreement; therefore the bvp4c is able to give accurate results. The effects of governing parameters on the flow and heat transfer characteristics are presented.